The management of didactic support systems at a nursing college - Pullen, A E; Botes, A C (Curationis (Pretoria), 1998)
The learning accompanists (nurse educator), in the didactic situation within the context of a nursing college, is midst a process of transformation. This transformation has a direct influence on the learning accompanists didactic role fulfilment. Didactic support systems enables the learning accompanist to fulfill her/his didactic role. These didactic support systems should be managed during the process of transformation, in such a way that it enables the learning accompanist to fulfil her/his didactic role. A new creative approach to the management of the didactic situation is necessary. The goal of this study was to describe guidelines for the management of didactic support systems, at a nursing college, to enable the learning accompanist to fulfil her/his didactic role. An inductive, qualitative, contextual, exploring, descriptive strategy was used to reach the goal of the study. No explicit conceptual framework was used as point of departure. Because the participants are midst a process of transformation, their knowledge and experience was used as source of data, as they can express their needs and views the best. The goal of this study was reached by setting four objectives. The uniqueness of the study lies in the relevance within the current time frame context and that it expresses the needs of the learner accompanists and the views of the managers at a nursing college. An abundance of possibilities for further research was created.